Emerging trends in the growth of structural systems for tall buildings. Issue 3 (2nd July 2020) - Memon, Shazim Ali; Zain, Muhammad; Zhang, Dichuan; Rehman, Sardar Kashif Ur; Usman, Muhammad; Lee, Deuckhang
ABSTRACT: Tall buildings are being built for more than a century now, but there has been an exponential growth in the development of convoluted tall buildings with distinctive architecture. A tall building with a unique structural form, brings forth admonishing challenges for the structural designers to deal with. Such a contemporary inclination towards the fabrication of free-form structures has posed enormous challenges to the modern-day structural engineering community, and consequently, has faced reactions in the form of tremendous researches pertaining to complex building specific issues. This paper extensively reviews six case studies of recent tall buildings that possess a challenging architecture with tortuous structural features to cope with the gravity and lateral loadings. Six representative tall buildings have been chosen from all over the world, which have distinctive features in terms of their structural systems. This paper discusses the fundamental characteristics of these tall buildings in the world and presents the challenges faced during the modelling, analysis, design, and construction of these skyscrapers, along with the brief of methodologies which were eventually adopted to cope with these challenges.